Critical Review: Biogeochemical Networking of Iron in Constructed Wetlands for Wastewater Treatment - Wu, Shubiao; Vymazal, Jan; Brix, Hans (Environmental science & technology, 2019)
Iron is present in all types of wastewater; however, besides acid mine drainage, where it is a major constituent of concern, it is usually neglected in other types of wastewaters. In all kinds of constructed wetlands, iron plays important role in removal of organics and phosphorus, and it has an impact on transformation of nitrogen, sulfur, and metals. The biogeochemistry of iron is well understood in natural wetlands, but knowledge about iron impact on microbiological and chemical transformations during wastewater treatment in constructed wetlands is very limited. So far, the sparse research in this area provides limited information on observed interactions with several varying parameters across the studies, making it difficult to draw fundamental and mechanistic conclusions. A critical review of the complex biogeochemical networking of iron in CWs is therefore necessary to fill the gap in knowledge on the role of iron and its biogeochemical multi-interactions in wastewater treatment processes of CWs. This review is the first with specific focus on iron, discussing its mitigation and retention in CWs with different configurations and operational strategies, and presenting both seasonal dynamics and the potential remobilization of Fe. It also comprehensively discusses the interactions of redox-controlled iron turnover with the biogeochemical processes of other elements, for example, carbon (C), nitrogen (N), phosphorus (P), sulfur (S), and heavy metals. The health response of wetland plants to both deficiency and toxicity of Fe in CWs designed with specific treatment targets has also been evaluated. Due to the complexity of various wastewater compositions and microredox gradients in the root rhizosphere in CWs, future research needs have also been identified.
Keywords: odpadní voda; mokřady; Iron; Wastewater; železo; Nitrogen; Wetlands; Waste Disposal, Fluid; dusík; odpad tekutý - odstraňování